Religion,civil society and good governance:The 'pertubuhan jamaah Islah Malaysia' (JIM) experience - Malik, Maszlee (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2012)
The ‘good governance’ agenda promoted by international institutions and otheraid agencies as part of the globalisation phenomenon proposes, amongst others, the activerole of civil society in the political process. Effective functioning of civil society is believed to be essential for “good” governance. Currently, the dynamism of global civil society movements has shifted to a new dimension to incorporate culture and faiths into thediscourse on development, economy, politics and governance in a more progressiveapproach. In tandem, faithand religion, have been identified empirically as anothermotivators for civil society activism, hence its distinctive role in development and goodgovernance. Such phenomenon has been addressed in the many circles of academia.Thispaper explores the role of faith in mobilizing civil society towards the achievement of what is known as “good governance” in Malaysia with Pertubuhan Jamaah Islah Malaysia (JIM)as a case study.